Progression of radial tears in L5-S1 intervertebral disc depends on location and type of movements: An in-silico study - Vinyas; Subraya Krishna Bhat; Hiroshi Yamada; Raviraja Adhikari; Shyamasunder Bhat N (PLoS ONE, 2026)
Low back pain is a global health challenge, with disc degeneration and annular tears contributing significantly to its onset and persistence. This numerical study evaluates how degeneration and the location of radial tears jointly influence the mechanical behavior of the L5–S1 spinal unit during flexion, extension, and lateral bending. A subject‑specific finite element (FE) model employing an anisotropic hyperelastic formulation was used to simulate healthy, mild, and moderate degeneration, along with radial tears spanning 75% of the annular width at four clinically relevant locations. Quantitative stress analysis revealed pronounced movement–tear location specificity, with posterior tears exhibiting approximately 4-6x higher boundary stresses during flexion, whereas anterior tears demonstrated 1.5-2x higher stresses during extension relative to other tear locations. Posterolateral (PL) tears exhibited their highest stresses during lateral bending, with PL1 (posterior‑shifted PL tear) showing 2-3x higher values and PL2 (more lateral PL tear) reaching 3-5x higher stresses compared to sagittal motions. Degeneration shifted the dominant stress contribution in PL2 from contralateral to ipsilateral lateral bending at the tear site, concurrently amplifying stress magnitudes in flexion and extension without altering the motion-dependent vulnerability patterns associated with each tear location. These findings offer biomechanical insights into how tear location and degeneration affect tear progression and may help guide clinicians in tailoring movement‑specific conservative or interventional treatment strategies.